2017
DOI: 10.1111/avsc.12326
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of lowland hay meadows and pastures in Western and Central Europe

Abstract: Questions Which are the main vegetation types of lowland hay meadows and pastures in Western and Central Europe? What are the main environmental gradients that drive patterns of species composition? Is it possible to classify these grasslands to phytosociological alliances that reflect management practices? Location Western and Central Europe (excluding the Alps and Carpathians). Methods A database of 21 400 vegetation plots of mesic grasslands across Western and Central Europe was compiled. After geographical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 25 publications
(48 reference statements)
0
36
0
1
Order By: Relevance
“…However, traits and taxonomic diversity may respond differently to changes in management, and their relationship is likely to be determined by the size of the local species pool, productivity of the system, and type of disturbance (Mayfield et al., ). A recent study showed that floristic composition of hay meadows in Western and Central Europe differed more in relation to management intensity than type (Rodríguez‐Rojo et al., ). Moreover, we need to consider that species diversity and composition are filtered in a hierarchical way (Catorci & Gatti, ) with the effects of local processes, such as management, driving plant–plant interaction and competition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, traits and taxonomic diversity may respond differently to changes in management, and their relationship is likely to be determined by the size of the local species pool, productivity of the system, and type of disturbance (Mayfield et al., ). A recent study showed that floristic composition of hay meadows in Western and Central Europe differed more in relation to management intensity than type (Rodríguez‐Rojo et al., ). Moreover, we need to consider that species diversity and composition are filtered in a hierarchical way (Catorci & Gatti, ) with the effects of local processes, such as management, driving plant–plant interaction and competition.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown the importance of management type and intensity in maintaining or modifying plant species richness and composition in grasslands (e.g Marini, Scotton, Klimek, Isselstein, & Pecile, ; Marini, Scotton, Klimek, & Pecile, ; Catorci, Cesaretti, Malatesta, & Tardella, ; Bonari et al., ; Rodríguez‐Rojo et al., ). On the other hand, other variables influence floristic composition, biodiversity and agronomic value of hay meadows: soil characteristics (Angiolini, Riccucci, & De Dominicis, ; Marini et al., ), topography‐related environmental factors (Bennie, Hill, Baxter, & Huntley, ; Gusmeroli et al., ), climatic (Herben, Krahulec, Hadincová, Pecháčková, & Wildová, ) and spatial factors (Di Giulio, Edwards, & Meister, ).…”
Section: Introductionmentioning
confidence: 99%
“…Lowland hay meadows are semi-natural communities where hay is most often obtained twice. They originated on fertile mineral soils (with a high share of silt or clays), in various morphological conditions and due to long-term not intensive agricultural use as mesic hay meadows [5,82]. They are composed of plant communities which often arise in river valleys usually outside the floodplain, on upper terraces where floods and inundation do not occur [83].…”
Section: Habitat 6510: Lowland Hay Meadowsmentioning
confidence: 99%
“…Their location in Poland is well known in Natura 2000 areas, but poorly recognized outside protected areas. Lowland mesic meadows are one of the richest species meadow habitats, very valuable particularly due to invertebrates, but also at high risk of transformation into arable land [82]. The community is characterized by high variability in terms of species composition (Galium mollugo, Campanula patula, Knautia arvensis, Rumex thyrsiflorus) as well as physiognomy [82]; to a small extent the community shows geographical variability.…”
Section: Habitat 6510: Lowland Hay Meadowsmentioning
confidence: 99%
“…of geographic patterns and main driving factors of species composition (Rodríguez-Rojo et al, 2017;Willner et al, 2017Willner et al, , 2019Marcenò et al, 2018). Vegetation classification studies have played a major role in the development of transnational European habitat typologies (Schaminée et al, 2016;Rodwell, Evans & Schaminée, 2018;Biurrun, Bergmeier, Dengler, Jansen & Willner, 2019) and their quality assessment Tsiripidis, Xystrakis, Kallimanis, Panitsa & Dimopoulos, 2018), which is an important basis for decision-making processes in nature conservation.…”
mentioning
confidence: 99%